Pengaruh Pemberian Sari Kurma dan Pijat Oksitosin Terhadap Produksi ASI - Habilah Nor Hofi Hofi; Widia Shofa Ilmia (Universitas Islam Jember, 2025)
This study was conducted to examine the impact of date extract administration and oxytocin massage on breast milk production in breastfeeding mothers at TPMB Habilah Nur Hofi, Baratan Village. The study employed a quasi-experimental method with a pretest-posttest design involving 30 breastfeeding mothers, divided into intervention and control groups. The intervention consisted of daily date extract consumption and oxytocin massage for seven days. Results showed a significant increase in breast milk production in the intervention group compared to the control group. In addition, supporting factors such as maternal nutritional status, breastfeeding frequency, and family support also contributed to the success of the intervention. The study concludes that the combination of date extract therapy and oxytocin massage effectively stimulates increased milk production and provides positive psychological benefits for the mother. It is recommended that this intervention be integrated into maternal and child health programs, especially in rural areas, to support the success of exclusive breastfeeding.